Accounting of Tumbilotohe: An Islamic Ethnomethodology Study - Thalib, Mohamad Anwar (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This study aims to construct accounting practices in the implementation of tumbilotohe culture. This study uses a spiritual paradigm with an Islamic ethnomethodology approach. There are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy. There were four informants in this study. The four informants were selected using a purposive sampling technique. The results of the study found that the capital for the implementation of tumbilotohe comes from natural resources that can be obtained and used free of charge by residents, donations by residents obtained through granting requests for financial assistance in the form of proposals and initiatives from residents. The practice of capital accounting is conditional on the value of sustenance from the Creator and help each other. These values are contained in the lumadu value